2016
DOI: 10.1051/parasite/2016016
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in infection with trematode species utilizing jellyfish as hosts: evidence of transmission to definitive host fish via medusivory

Abstract: In the Seto Inland Sea of western Japan, metacercariae of three species of trematodes, Lepotrema clavatum Ozaki, 1932, Cephalolepidapedon saba Yamaguti, 1970, and Opechona olssoni (Yamaguti, 1934), were found in the mesoglea of the jellyfish Aurelia aurita s.l., Chrysaora pacifica, and Cyanea nozakii. Moreover, these jellyfish frequently harbored juveniles of the fish species Psenopsis anomala, Thamnaconus modestus, and Trachurus japonicus. The former two fish species are well-known medusivores. We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Many fish are known to be associated with jellyfish mainly for the reasons of antipredation and/or feeding (Mansueti 1963, Arai 1988, 2005, Ates 1988, Bonaldo et al 2004, Ohtsuka et al 2009. Some medusivorous fish, such as filefish, seem to consume not only scyphomedusae, but also cubomedusae, as food (Arai 1988, 2005, Ates 1988, Purcell & Arai 2001, Bonaldo et al 2004, Masuda 2009b, Miyajima et al 2011, Kondo et al 2016. Our observation of the feeding behavior by Thamnaconus modestus on M. virulenta clearly confirmed that cubomedusae were eaten by the fish.…”
Section: Symbioses Between Cubomedusae and Fishsupporting
confidence: 76%
“…Many fish are known to be associated with jellyfish mainly for the reasons of antipredation and/or feeding (Mansueti 1963, Arai 1988, 2005, Ates 1988, Bonaldo et al 2004, Ohtsuka et al 2009. Some medusivorous fish, such as filefish, seem to consume not only scyphomedusae, but also cubomedusae, as food (Arai 1988, 2005, Ates 1988, Purcell & Arai 2001, Bonaldo et al 2004, Masuda 2009b, Miyajima et al 2011, Kondo et al 2016. Our observation of the feeding behavior by Thamnaconus modestus on M. virulenta clearly confirmed that cubomedusae were eaten by the fish.…”
Section: Symbioses Between Cubomedusae and Fishsupporting
confidence: 76%
“…Therefore, we assume that this 293 spatial variation in the parasite prevalence could be related to a spatial variation of the primary host 294 (gastropod) densities, as well as of that of the definitive host. Parasite prevalence also remained 295 high throughout the year, a range similar to that reported elsewhere for Posthodiplostomum cuticula 296(Ondráčková et al 2004a) or other digeneans(Mbokane et al 2015;Kondo et al 2016). Maximum 297 prevalence (100%) was observed in autumn, and then prevalence decreased in winter, due to the 298 presence of both juvenile and adult metacercariae-free fish.…”
supporting
confidence: 77%
“…Trachurus species are a main prey item of Arripis trutta in south-eastern Australia (Hughes et al, 2013). Trachurus species are known to associate with jellyfish (Masuda et al, 2008;Kondo et al, 2016) and, thus, seem a likely pathway for O. kahawai to reach S. lalandi and species of Arripis.…”
Section: Opechona Cf Kahawaimentioning
confidence: 99%